Comparative Analysis of Single-Cell Transcriptome Data Reveals a Novel Role of Keratinocyte-Derived IL-23 in Psoriasis - Park, Young Joon; Kim, Yul Hee; Lee, Eun-So; Kim, You Chan (Frontiers in Immunology, 2022)
Psoriasis, a common inflammatory skin disease, is critically dependent on the IL-23/IL-17 cytokine axis. Although immune cell-derived IL-23 is generally associated with the disease pathogenesis, there have been reports of IL-23 production in keratinocytes. To determine the presence and potential role of keratinocyte-derived IL-23 in psoriasis, we investigated its expression levels using publicly available single-cell RNA sequencing data from human samples. We discovered that the expression of IL23A was detectable in keratinocytes as well as dendritic cells. Furthermore, we examined the IL-23p19 expression in an imiquimod-induced mouse model of psoriasis and found a close relationship between keratinocyte-produced IL-23 and IL-36, another key cytokine in psoriasis pathogenesis. The blockade of IL-23 signaling resulted in the reduced expression of IL-36 in the keratinocytes. Our findings reveal the novel association between keratinocyte-derived IL-23 and IL-36 in psoriasis progression.